Intergenerational management at GlaxoSmithKline in Asia Pacific - LUTHRA, Poornima (Institutional Knowledge at Singapore Management University, 2014)
In September 2013, Kimberly Wong, an external consultant working with GlaxoSmithKline (GSK), a large multinational healthcare company, is tasked with evaluating and improving GSK’s HR strategy in Asia Pacific on how well it addresses talent gaps and intergenerational workforce issues. This is an important issue that the region faces since economic growth outpaces population growth, resulting in chronic talent shortages. In this environment, talent, especially among the Generation Y cohort born between 1981 and 2001, is spoiled for choice, as evidenced by stark attrition rates. GSK must not only attract talent, but also develop that talent and retain them in order to overcome the talent gap. This issue becomes particularly acute for general management and other senior positions as the older Baby Boomer generation, born between 1946 and 1960, retires; and the smaller Generation X cohort, born between 1961 and 1980, is insufficient in size to take up the mantle. With three generations in the workforce, Wong needs to consider how best to develop future talent and leadership by motivating each generation while being fair and impartial. Intergenerational tensions could easily arise through ill- conceived HR policies, inadequate HR tools or even the wrong leadership style. Diminished performance and higher attrition rates are very real consequences. This case confronts students with the challenges of managing intergenerational workplace diversity and talent management. It is suitable for undergraduate, graduate and executive level classes.